Pérenniser le patrimoine immatériel : un projet d’archivage logiciel mis en place par l’Aconit - Antoine Hébert; Xavier Hiron (Humanités Numériques)
The article discusses the challenges of preserving software as part of the Association pour un conservatoire de l’informatique et de la télématique (Aconit), a French nonprofit organisation for heritage computer science. One major issue is the decreasing availability of hardware and compatibility with older computer systems, which makes it difficult to maintain and preserve software for extended periods of time. Additionally, the magnetic materials that make up the storage media can degrade over time, making it impossible to retrieve the digital data they contain. With over 3,700 media potentially affected, the scale of this project is significant. Despite these challenges, preserving such software is important because it provides insight into scientific, social and human activities, and is therefore an important part of our cultural heritage. This article discusses the theoretical and practical aspects of this preservation effort, including examples and technical considerations. It also considers the broader implications of this work for the digital humanities and social sciences. Despite these challenges, preserving the software is important because it provides insight into scientific, social, and human activities, and is therefore an important part of our cultural heritage.